Covalent organic frameworks derived carbon supported cobalt ultra-small particles: CO and Co-Nx complex sites activated peroxymonosulfate synergistically for efficient degradation of levofloxacin. (15th November 2022) - Cao, Min; Lei, Juying; Zhang, Jinlong; Zhou, Liang; Liu, Yongdi
Abstract: Recently, the carbon materials with metal-Nx sites or carbonyl (CO) have attracted extensive attention in the degradation of organic pollutants for peroxymonosulfate (PMS) activation. However, the synergistic mechanism of different sites for PMS activation is not clear. In this study, covalent organic frameworks (COF) derived carbon materials (Co–C500COF ) with abundant CO and ultra-small Co particles were synthesized by simple hydrothermal and calcination. Theoretical and experimental results revealed that the introduction of cobalt species formed the Co-Nx site, which was beneficial to the release of CO which originally blocked by N group in COF. The results indicated that Co–C500COF showed excellent catalytic activity, which resulted in 94.3% of levofloxacin (LVX) removal within 2h for PMS activation, and good stability, 80% degradation efficiency after five cycles. The Co–C500COF /PMS system also maintained the incredible degradation effects in a wide pH range (3–9) and complex water environment with ion interference, which made it more potential for industrial application. The mechanism exploration revealed that CO and cobalt and nitrogen coordination (Co-Nx) sites were related to the production of singlet oxygen ( 1 O2 ) in the main active reactive species. The degradation intermediates and toxicity of LVX were also evaluated, possible degradation pathways were proposed, and most intermediates were more environmentally friendly than LVX. Our catalyst is an ideal catalyst for the removal of organic pollutants from actual wastewater. Graphical abstract: Image 1